Periodontal treatment in a generalized severe chronic periodontitis patient: A case report with 7-year follow-up - AĞRALI, ÖMER BİRKAN (My University, 2015)
The aim of the periodontal treatment is to provide healthy and functional dentition all through a lifetime. In this report, periodontal treatment of a 42‑year‑old male patient with generalized severe chronic periodontitis is presented. He received initial periodontal treatment together with adjunctive antimicrobials. The devital teeth were endodontically treated, and free gingival grafts were placed at the inadequate keratinized tissue zones before regenerative surgery. Following the surgical treatment using enamel matrix derivatives and xenogenic bone graft combination, the patient was put on a strict recall program. After 12 months, favorable clinical and radiographical improvements were obtained. The 7‑year maintenance of the present case with several initially hopeless teeth has been shown and discussed in this report. It can be concluded that optimum oral hygiene level as well as the positive cooperation of the patient enhanced the success of periodontal treatment results even in extremely severe periodontal destruction.
Periodontal treatment in a generalized severe chronic periodontitis patient